Comparison of results of revision total knee arthroplasty surgery due to septic and aseptic loosening - Fatih Dogar; Okkes Bilal; Duran Topak; Mustafa Abdullah Ozdemir; Burak Kuscu (Medicine Science, 2021)
The purpose of this study was to share the clinical, functional and radiological results of patients who underwent revision total knee arthroplasty (RTKA) for septic or aseptic loosening after total knee arthroplasty. 34 patients who were diagnosed with septic (n=19) or aseptic (n = 15) loosening after total knee arthroplasty and underwent single stage (aseptic group) or two-stage (septic group) RTKA surgery between May 2015 and June 2020 were analyzed retrospectively. Patients with septic loosening were checked again with clinical and laboratory evaluations for the second stage of revision surgery at the postoperative 3rd and 6th weeks. The changes in the joint line before and after the surgery were measured radiographically. The classification of the defects was performed by using the Anderson Orthopedic Research Institute criteria. Preoperative and postoperative Knee Society Score (KSS) was completed by all patients. KSS scores were a statistically significant increase observed in the postoperative values compared to the preoperative ones in both groups (p = 0.001). Moreover, there was a statistically higher increase observed among the aseptic loosening patients compared to the septic patients and the preoperative period in the KSS scores (p = 0.001). In terms of the preoperative distance between the fibular styloid and distal part of the femoral component used in the evaluation of the joint line, it was observed that postoperatively, there was a higher increase in among the patients with septic loosening TKA compared to the aseptic loosening TKA (p = 0.002). As a result, restoration of the joint line is a very important parameter in RTKA, and the increase in joint distance negatively affects the results clinically and functionally. Two-stage surgical treatment in septic loosening TKA is an effective and successful surgical method for the prevention reinfection. [Med-Science 2021; 10(3.000): 706-13]